Development of Microfluidic, Serum-Free Bronchial Epithelial Cells-on-a-Chip to Facilitate a More Realistic In vitro Testing of Nanoplastics - Gupta, Govind; Vallabani, Srikanth; Bordes, Romain; Bhattacharya, Kunal; Fadeel, Bengt (Frontiers in Toxicology, 2021)
Most cell culture models are static, but the cellular microenvironment in the body is dynamic. Here, we established a microfluidic-based in vitro model of human bronchial epithelial cells in which cells are stationary, but nutrient supply is dynamic, and we used this system to evaluate cellular uptake of nanoparticles. The cells were maintained in fetal calf serum-free and bovine pituitary extract-free cell culture medium. BEAS-2B, an immortalized, non-tumorigenic human cell line, was used as a model and the cells were grown in a chip within a microfluidic device and were briefly infused with amorphous silica (SiO2) nanoparticles or polystyrene (PS) nanoparticles of similar primary sizes but with different densities. For comparison, tests were also performed using static, multi-well cultures. Cellular uptake of the fluorescently labeled particles was investigated by flow cytometry and confocal microscopy. Exposure under dynamic culture conditions resulted in higher cellular uptake of the PS nanoparticles when compared to static conditions, while uptake of SiO2 nanoparticles was similar in both settings. The present study has shown that it is feasible to grow human lung cells under completely animal-free conditions using a microfluidic-based device, and we have also found that cellular uptake of PS nanoparticles aka nanoplastics is highly dependent on culture conditions. Hence, traditional cell cultures may not accurately reflect the uptake of low-density particles, potentially leading to an underestimation of their cellular impact.